HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT PADA KLIEN DENGAN SKIZOFRENIA PARANOID - Ediawati, Riska; Sari, Yunita (Journal of Smart Nursing and Health Science, 2025)
Background: Paranoid schizophrenia is a severe mental disorder that significantly impacts patients' quality of life, with high relapse rates due to medication non- adherence. Family support plays a crucial role in ensuring adherence. Objective: This study aims to analyze the relationship between family support and medication adherence in patients with paranoid schizophrenia in the Mandala Health Center, Lebak Regency. Methods: This correlational analytic study employed a cross- sectional approach. A total of 30 respondents were selected using total sampling. Data were collected through validated questionnaires and analyzed using the chi- square statistical test. Results: The findings indicate a significant relationship between family support levels and medication adherence, with a p-value 0.021 (< 0.05). Patients with good family support demonstrated higher adherence levels compared to those with less support. Conclusion: There is a relationship between family support and medication adherence in adults with paranoid schizophrenia in the Mandala Health Center, Lebak Regency